Effect of isolation conditions on structural properties and surface behavior of soy-whey proteins. Issue 2 (2018) - Ingrassia, Romina; Sobral, Pablo Antonio; Risso, Patricia Hilda; Palazolo, Gonzalo Gastón; Wagner, Jorge Ricardo
No abstract available